Revista de Gastroenterologia del Peru: Bibliometric Analysis-decade 2010-2019 - Bardales-Silva, Angel Fabrizzio (2023)
The objective was to design a bibliometric analysis of the Revista de Gastroenterologia del Peru’s scientific publications. We conduct bibliometric retrospective research. All articles of Revista de Gastroenterologia del Peru since 2010 to 2019 were considered. The sample included: original articles, review articles, case reports, special articles and letters. Production, impact and collaboration bibliometric index were assessed. 514 publications were analyzed. The total production remained in a range between 46 to 76 publications per year, with an average of 4.89 authors per article. The Impact factor - Scimago Journal Rank- was between 0.12 to 0.157 and h-index of 8. The most cited article received 14 citations. A co-authorship network composed of 91 nodes and 11 clusters, and an institutional collaboration network of 16 nodes and 5 clusters were designed. The production and impact index show an upward trend compared to previous values of the journal and comparative way with other publications in South America, while the collaboration indicators are incipient, yet.